Effects of local farming practices on soil organic carbon content, enzymatic activities, and microbial community structure in semi-arid soils of Morocco - Jindo, Keiji; El Aroussi, Omar; de Vente, Joris; López Carratalá, Jorge; Bastida, Felipe; Izquierdo, Carlos Garcia; Sawada, Yoshito; Goron, Travis L.; Barberá, Gonzalo G. (Frontiers in Soil Science, 2024)
Soil organic carbon (SOC) is essential in semi-arid agricultural land for enhancing soil health, particularly through the promotion of microbial activities. This study assessed the impact of different agronomic practices on soil properties, microbial communities, and SOC levels in semi-arid Moroccan wheat fields. Three treatments were investigated: eucalyptus (Eucalyptus spp.) companion planting (EU), and fallowing with harvest residue mulching (FA), with the latter involving both short (3 months; FAS) and long (15 months; FAL) fallow periods. The study revealed significant variation in soil characteristics and microbial communities between these agronomic management regimes. Notably, soils managed with FAL contained elevated SOC levels (1.2%) compared to other treatments (FAS and EU) which show lower SOC range (0.62-0.86%). Both labile C (water-soluble carbon) and recalcitrant C (humic substances) were increased by FAL. Additionally, soil microbial biomass and dehydrogenase activity were observed to be high in FAL-managed soils, along with increased levels of extracellular enzymes related to nutrient cycling (β-glucosidase, alkaline phosphatase, and urease). Phospholipid fatty acid (PLFA) analysis indicated positive correlation between carbon content in soils and microbial populations. In contrast, soils managed with EU had significantly lower SOC levels, possibly due to differences in carbon fractionation. FAL increased soil enzymatic activities and enriched the microbial community when compared to EU management. In conclusion, this study indicated the importance of fallowing and fallowing period for conservation of SOC, and potential to mitigate negative effects of biophysical constraints on agricultural productivity in semi-arid soils of Northwest Africa.